ANALISIS MOTIVASI BELAJAR BIOLOGI SISWA KELAS VIII MTs SEJAHTERA BERSAMA RAMBAH SAMO TAHUN PEMBELAJARAN 2014/2015 - -, Iswandi; Lestari, Rena; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about analysis of student motivation learning on biology class VIII Student of MTs Sejahtera BersamaRambah Samo Prosperity Learning on Year 2014/2015 has been conducted in December 2014 to January 2015with a descriptive qualitative method. Sample was collected by using total sampling technique. Results showedthat the analysis of the eight indicators in this study showed an average percentage of 73% with the high category